Urgensi pengembangan TPACK bagi guru bahasa Indonesia - Etheldredha Tiara Wuryaningtyas; Yuliana Setyaningsih (BAHASTRA, 2020)
TThe objectives of this reseaerch were to describe: (1) Teachers’ competencies in integrating Technological Pedagogical Content Knowledge (TPACK) in lesson plan; (2) The urgency of developing TPACK for Indonesian junior high school teachers. The type of research was the descriptive research with the lesson plans of Indonesian junior high school teachers as substantive data source. The locative data source of this research was the junior high schools in Gunungkidul Regency, Yogyakarta. The data collection technique is done by using document observation and questionnaires. This technique is used to obtain identification of the lesson plan components related to Pedagogical Content Knowledge (PCK) and Technological Content Knowledge (TCK). Data were analyzed by using descriptive statistic method to show the degrees of mastery percentage of Indonesian teachers’ PCK and TCK. The conclusions of this study were stated as follows: (1) the ability of teachers to integrate technology is still limited to the use of PowerPoint, (2) the learning resources used by teachers are still limited to conventional textbooks, not the technology-based online sources, (3) the integration of technology by teachers in preparing lesson plans is still minimum, and (4) teachers are already using technology, but are still limited to CAI (Computer Assisted Instruction). Based on the research results above, it is concluded that the development of TPACK for Indonesian language teachers at the junior high school level is urgent.